Waves And Instabilities In Plasmas (World Scientific Lecture Notes in Physics) - Chen Liu (World Scientific, 1987)
The topics covered in these notes are selective and tend to emphasize more on kinetic-theory approaches to waves and instabilities in both uniform and non-uniform plasmas, students are assumed to have some basic knowledge of plasma dynamics in terms of single-particle and fluid descriptions.